Pendidikan Inklusif: Hak Pendidikan bagi Semua Anak Indonesia - Juwantho Lewa, Muhammad (UNIVERSITAS SERAMBI MEKKAH, 2025)
Inclusive education is an education system that provides equal opportunities for all children, regardless of background, physical condition, or intelligence level. In Indonesia, inclusive education is increasingly seen as an important step in realizing the right to education for all children, including children with special needs. The article will discuss the concept of inclusive education, the challenges of its implementation in Indonesia, and the role of government, schools, and society in ensuring equitable and quality education for all children. Inclusive education is expected to reduce social disparities, encourage social integration, and provide wider and fairer access to education for all children of the nation.